Topics on Analysis in Metric Spaces - Ambrosio, Luigi (Oxford Lecture Series in Mathematics and Its Applications Ser., 2003)
Based on lecture notes from the Scuola Normale this book presents the main mathematical prerequisites for analysis in metric spaces. Supplemented with exercises of varying difficulty it is ideal for a graduate-level short course for applied mathematicians and engineers.